Socs3b regulates the development and function of innate immune cells in zebrafish - Sobah, Mohamed L.; Scott, Aimee C.; Laird, Miranda; Koole, Cassandra; Liongue, Clifford; Ward, Alister C. (Frontiers in Immunology, 2023)
Suppressor of cytokine signaling 3 (SOCS3) is a critical component of the negative feedback regulation that controls signaling by cytokines and other factors thereby ensuring that important processes such as hematopoiesis and inflammation occur at appropriate levels. To gain further insights into SOCS3 function, the zebrafish socs3b gene was investigated through analysis of a knockout line generated using CRISPR/Cas9-mediated genome editing. Zebrafish socs3b knockout embryos displayed elevated numbers of neutrophils during primitive and definitive hematopoiesis but macrophages numbers were not altered. However, the absence of socs3b reduced neutrophil functionality but enhanced macrophage responses. Adult socs3b knockout zebrafish displayed reduced survival that correlated with an eye pathology involving extensive infiltration of neutrophils and macrophages along with immune cell dysregulation in other tissues. These findings identify a conserved role for Socs3b in the regulation of neutrophil production and macrophage activation.